Էդուարդ Հայրապետյանի դաշնամուրային կվարտետը - Կարապետյան, Գոհար
Սույն հոդվածում քննության է առնվել կոմպոզիտոր Էդուարդ Հայրապետյանի «Դաշնամուրային կվարտետը», որն իր ուրույն տեղն է զբաղեցնում թե՛ կոմպոզիտորի և թե՛ հայկական կամերային-գործիքային երաժշտության մեջ։ Դաշնամուրային տրիոն (ջութակ, թավջութակ և դաշնամուր) կոմպոզիտորը գրել է 1981 թվականին, սակայն որոշ ժամանակ անց՝ 1998 թվականին այն վերափոխել է և դարձրել Դաշնամուրային կվարտետ (ջութակ, ալտ, թավջութակ և դաշնամուր)։ Դաշնամուրային կվարտետն ինքնատիպ է իր ձևակառուցվածքով. բացակայում է թեմատիկ զարգացումը՝ այսինքն վարիացիոն ձևում է: Վարիացիայի անցումը մյուսին քողարկված չէ, այլ հստակ երևում է։ In this article we deal with the piano quartet of the composer Eduard Hayrapetyan. This musical work has its incomparable place both in the creative activity of the composer and in the Armenian chamber instrumental music. Eduard Hayrapetyan is one of the prominent representatives of the Armenian composer school. He created European classic music derived from Armenian professional musical traditions, synthesized contemporary melodic elements with folk and with folk - professional elements. He also responded with great interest to the contemporary professional musical structure and in this way created his own special composer way. In 1981 he created the Piano trio for violin, cello and piano. However, in 1988 he transformed the trio into the piano quartet (violin, viola, cello and piano). The Piano quartet is unique by its composition. It lacks the general thematic development, i.e. it is based on the mutual transition of the variations, which is expressed very brightly.
Keywords: Արվեստագիտություն